Growth and production of cat's whiskers plant biomass (Orthosiphon aristatus Bl. Miq.) In various accessions and harvest intervals - Figono, Adinda Putri; Budiman, Budiman; Huda, Adinda Nurul (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Cat's whiskers plant is an ornamental plant used as a medicinal plant. The part of the cat's whiskers plant used is leaves. Accessions and harvest intervals are essential for increasing optimal yields to plant biomass growth and results. This study aims to determine the effect of differences in accession, intervals, and interactions between accession differences and intervals on the growth and production of a cat's whiskers biomass. The design used in this study is a complete group design of being randomized with two treatment factors. The first factor has two treatment levels: white flowering accessions (A1) and purple flowering accessions (A2). The second factor is a harvest interval with four treatment levels, namely a 1-week harvest interval (P1), two weeks (P2), three weeks (P3), and six weeks (P4). The results showed that accession treatment significantly affected the number of books, number of branches, flowering ages, leaf fresh weight, leaf dry weight, and leaf simplicia yields. Harvest interval treatment significantly affects the height of the shoots, number of shoots, number of branches, number of leaves, flowering ages, leaf fresh weight, stem fresh weight, flower fresh weight, leaf dry weight, stem dry weight, flower dry weight, and leaf simplicia yield. Accession interactions with harvest intervals significantly affect the height of the shoots, number of shoots, number of branches, number of leaves, flower fresh weight, stem dry weight, and leaf simplicia yields.